2011
DOI: 10.1073/pnas.1107304108
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the metabotropic glutamate receptor 5 (mGluR5) induces melanoma in transgenic mice

Abstract: Glutamate is the major excitatory neurotransmitter in the mammalian CNS and mediates fast synaptic transmission upon activation of glutamate-gated ion channels. In addition, glutamate modulates a variety of other synaptic responses and intracellular signaling by activating metabotropic glutamate receptors (mGluRs), which are G protein-coupled receptors. The mGluRs are also expressed in nonneuronal tissues and are implicated in a variety of normal biological functions as well as diseases. To study mGluR-activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(78 citation statements)
references
References 40 publications
2
75
0
Order By: Relevance
“…More recently, Choi et al (2011) showed that mice in which metabotropic glutamate receptor 5 (mGluR5) expression was driven by the Trp1 promoter also developed murine melanomas with high penetrance. Furthermore, mGluR5 expression could be documented in human melanomas and may provide an oncogenic signal through ERK (Choi et al 2011).…”
Section: Glutamate Receptor Dysfunctionmentioning
confidence: 99%
“…More recently, Choi et al (2011) showed that mice in which metabotropic glutamate receptor 5 (mGluR5) expression was driven by the Trp1 promoter also developed murine melanomas with high penetrance. Furthermore, mGluR5 expression could be documented in human melanomas and may provide an oncogenic signal through ERK (Choi et al 2011).…”
Section: Glutamate Receptor Dysfunctionmentioning
confidence: 99%
“…Recently, ectopic expression of the other group I metabotropic glutamate receptor, mGRM5, has been shown to also produce melanoma in a second transgenic model (13). …”
Section: Introductionmentioning
confidence: 99%
“…A significant decreased level of glutamate in melanoma group suggests that the above mentioned pathways may have been profoundly disturbed. Glutamate signaling in cancer has stimulated extensive research interest recently and has shown great importance in human melanoma development (Namkoong et al 2007; Choi et al 2011; Stepulak et al 2005; Rzeski et al 2001). The blockade of glutamate receptors has been proposed as a promising novel therapy for treating melanoma (Song et al 2012).…”
Section: Resultsmentioning
confidence: 99%